Bariatric surgery: nurse's role in post-surgery quality of life (Research, Society and Development, 2022)
The Nursing Process follows a protocol that is divided into five stages: investigation, diagnosis, planning, implementation and evaluation of nursing care. It is an exclusive activity of the Nurse, the professional responsible for directing all the work developed by their nursing team. The objective of this study is based on an analysis of the literature on the nursing care process for patients in the pre and postoperative period of bariatric surgery and to highlight the notoriety of public policies for humanization in the care provided to patients in the pre and postoperative period. of bariatric surgery. The methodology is anchored in a qualitative approach, resorting to the use of bibliographic research. The results and discussions showed that this is a process that deserves attention because it considers that the nursing follow-up helps in the adaptation of the patient after surgery, minimizes complications and consequently influences his recovery. This study is necessary for other researches that enable educational strategies for the professional nurse and encourage good practice in health care.